UNITY OF THEORY AND PRACTICE IN THE PROMOTION OF PRESCHOOL CHILD'S MUSICALITY IN THE TEACHER'S AND CHILD'S COLLABORATION - Līduma, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
This scientific article involves holism, anthropological and action methodological approaches. The article includes theoretical substantiations based on J.Greata's (2006) concepts of the musical activity impact on the child holistic entirety development, B.Vikmane (1995) and L.Mackevicha's (1999), Latvian preschool music scientists, conceptions about music content and A.Liduma's (2004-2016) researches in the child musicality (emotional responsiveness, musical hearing, sense of rhythm, musical memory and musical thinking, voice vocal range and singing skill) development promotion possibilities through the teacher and the child collaboration in the preschool music sessions. The empiric research analyzes the integrity of theory and practice in the music  teacher pedagogical action at the integrative music session at preschool with 3-6-year-old children in x primary school at the preschool interest education. Conclusions are drawn that the child's positive attitude to his/her musicality development is promoted due to the scientifically substantiated music content accordant to the children needs, the teacher's orientation and skill to create in equality based collaboration with children.